Development of Smart Storage for CNC Tools Holder for Improving the Safety and Ease of Use of Tool Storage Systems - Rosli, Muhammad Shahrizan; Yusof, Yusri (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This project presents the development of a Smart Storage System for CNC Toolholders designed to enhance the security, efficiency, and user convenience of tool management in modern manufacturing environments. Traditional tool storage solutions often rely on manual locking mechanisms and offer limited user authentication, resulting in potential security vulnerabilities and operational inefficiencies. To address these issues, the proposed smart storage system integrates a suite of advanced technologies, including RFID-based access control, a solenoid lock, an infrared (IR) sensor, an OLED display, and a buzzer for alerts. Authorized users can access the toolholder by scanning their RFID tags, while unauthorized access attempts trigger an audible alarm and a warning message on the display. The IR sensor provides continuous monitoring of tool presence, with real-time updates shown on the OLED screen. All interactions including access events and toolholder status are logged via the serial monitor for monitoring and troubleshooting purposes. Survey feedback indicates strong user support, with over 90% agreeing that RFID access is essential to meet current technological standards. The Smart Storage System for CNC Toolholders demonstrates a reliable, scalable, and user-friendly solution adaptable to various industrial applications, showcasing the potential of integrating smart technologies into conventional storage systems.